Skills training through strategic Learning - Huerta Rosales, Moisés (2015)
Analyzes the influence of skills training through strategic learning, for which a methodology of explanatory causal research was used, combined with interpretative methodology, as the unit of analysis the context of university students was considered. The study explains the benefits of complex systems approach to skills training in macro and micro level curriculum, with teaching strategies focused on problem solving and evaluative approach focused on the evaluation of performance. In this context, the formation of strategic learning is a process that goes from external regulation to self-regulation, external control, mediated a regulation, culminating in the autonomous performance.